2020
DOI: 10.1113/jp279560
|View full text |Cite
|
Sign up to set email alerts
|

Is bilateral corticospinal connectivity impaired in patients with chronic obstructive pulmonary disease?

Abstract: During moderate and high levels of quadriceps force production, the ipsilateral motor cortex is concomitantly activated with the contralateral motor cortex throughout the corpus callosum to generate the motor command. r Chronic obstructive pulmonary disease (COPD) patients display a structurally impaired corpus callosum that may explain the reduced motor command in this population, which in turn contributes to COPD-related muscle weakness of the knee extensors. r The study aimed to determine whether bilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In recent years, white matter myelination has come to prominence as an underappreciated regulator of brain function, with studies demonstrating new roles such as trophic support of axons (Fünfschilling et al, 2012;Nave, 2010) and also plastic potential (Sampaio-Baptista et al, 2013). Moreover, several strains of evidence have highlighted that myelination influences cognition and behaviour in ageing and in a range of pathologies (Cabibel et al, 2020;Forbes et al, 2020;Hill et al, 2018;Lakhani et al, 2017;Ruckh et al, 2012;Shen et al, 2008;Weil et al, 2016;Zonouzi et al, 2015). Therefore, it would make sense for inter-individual variability in myelin to also play an important role in cognition and behaviour in health (Dubbioso et al, 2021), and potentially to underpin the previously reported relevance of white matter variability to wide-ranging behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, white matter myelination has come to prominence as an underappreciated regulator of brain function, with studies demonstrating new roles such as trophic support of axons (Fünfschilling et al, 2012;Nave, 2010) and also plastic potential (Sampaio-Baptista et al, 2013). Moreover, several strains of evidence have highlighted that myelination influences cognition and behaviour in ageing and in a range of pathologies (Cabibel et al, 2020;Forbes et al, 2020;Hill et al, 2018;Lakhani et al, 2017;Ruckh et al, 2012;Shen et al, 2008;Weil et al, 2016;Zonouzi et al, 2015). Therefore, it would make sense for inter-individual variability in myelin to also play an important role in cognition and behaviour in health (Dubbioso et al, 2021), and potentially to underpin the previously reported relevance of white matter variability to wide-ranging behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Given previous evidence of callosal damage in COPD patients, in a recent issue of The Journal of Physiology Cabibel and colleagues (2020) hypothesized that connectivity between the primary motor cortices may be disrupted. To test this, they used transcranial magnetic stimulation (TMS) to measure interhemispheric connectivity in a case–control design comparing 22 COPD patients with 21 age and sex‐matched controls.…”
Section: One Connectivity Many Connectivitiesmentioning
confidence: 99%
“…In this issue of The Journal of Physiology , Cabibel et al . (2020) explored bilateral neuromotor connectivity in patients with chronic obstructive pulmonary disease (COPD). While COPD is typically known for its debilitating effect on respiratory function, patients also suffer from muscle weakness and atrophy, leading to increased risk of falls and reduced quality of life.…”
mentioning
confidence: 99%